Bloodstream Infection Caused by Mucor velutinosus. Issue 1 (January 2016) - Racsa, Lori D.; Willis, Brian; Lockhart, Shawn R.; Kraft, Colleen S.
Abstract : Abstract: A 74-year-old man with diffuse large B-cell lymphoma was admitted to our institution for chemotherapy treatment. He developed a neutropenic fever, and blood cultures were drawn. After 48 hours from the time of draw, 2 of 2 blood culture bottles flagged positive. Thin, septate hyphae were seen on Gram stain of both blood culture bottles. In 1 day, gray fluffy mold began growing on chocolate agar plates from both of the positive bottles. A tease prep revealed a Mucorales sporangiophore. The specimen was sent out for further identification, and sequencing identified the mold as Mucor velutinosus .